OPTIMALISASI PEMASARAN DIGITAL PRODUK MINYAK SERAI UMKM GAYO LUES DALAM MEMBANGUN CITRA GREEN ECONOMY YANG KOMPETITIF - Zati, Muhammad Rizqi; Rosalina, Dhian; Maulidan, Rahmat (Universitas Mataram, 2025)
The rapid advancement of digital technology and increasing consumer awareness of environmental issues have driven micro, small, and medium enterprises (MSMEs) to evolve in two key areas: digitalization and business sustainability. However, many MSMEs in remote regions, such as Tripe Jaya Subdistrict in Gayo Lues Regency, still encounter several challenges, including low digital literacy, traditional marketing methods, and a limited understanding of green marketing practices. This community engagement initiative aims to enhance the digital capabilities and business sustainability of MSMEs that produce lemongrass oil through training and mentoring focused on technology and green marketing principles. The approach includes conducting initial assessments, providing digital and green marketing training, and implementing participatory-based monitoring and evaluation. The program's outcomes indicate significant improvements across four key areas: understanding of green production improved from 10% to 70%, local production skills increased from 35% to 80%, digital marketing proficiency rose from 30% to 90%, and environmental awareness grew from 20% to 85%. Additionally, the partner MSMEs successfully developed digital catalogs, adopted eco-friendly packaging, created marketplace accounts, and utilized social media for promotion. The mentoring process also included students as learning partners through the Merdeka Belajar Kampus Merdeka (MBKM) program, providing them with hands-on experience in developing science-based, practical solutions. This initiative demonstrates that integrated and participatory training methods can accelerate the digital transformation of MSMEs and establish a foundation.